2013
DOI: 10.1016/j.jvs.2012.06.101
|View full text |Cite
|
Sign up to set email alerts
|

Left subclavian artery coverage during thoracic endovascular aortic aneurysm repair does not mandate revascularization

Abstract: LSA coverage does not appear to result in an increased incidence of SCI or CVA event when a strategy of selective revascularization is adopted. Selective LSA revascularization results in similar outcomes among the three cohorts studied. Revascularization in women carries an increased risk of a CVA event and should be reserved for select cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 18 publications
2
82
1
Order By: Relevance
“…For example, Feezor et al described their experience with TEVAR and LSA coverage, and noted a reduction in stroke events from 6% down to 2% with selective revascularization. However, our results are in contrast to a contemporary study by Maldonado et al (12), that evaluated selective LSA revascularization during TEVAR patients with thoracic aortic aneurysm. This study noted a stroke rate of approximately 6%, with no difference in stroke outcomes with or without revascularization.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, Feezor et al described their experience with TEVAR and LSA coverage, and noted a reduction in stroke events from 6% down to 2% with selective revascularization. However, our results are in contrast to a contemporary study by Maldonado et al (12), that evaluated selective LSA revascularization during TEVAR patients with thoracic aortic aneurysm. This study noted a stroke rate of approximately 6%, with no difference in stroke outcomes with or without revascularization.…”
Section: Discussioncontrasting
confidence: 99%
“…40,42 During endovascular repair, guidewires within the aortic arch have the potential to mobilize debris and guidewire manipulation should be reduced to the minimum. According to a recent retrospective, multicentre analysis of selective LSA revascularisation in the treatment of multiple DTA pathologies, 48 coverage of the LSA in patients treated with TEVAR was associated with a higher incidence of stroke and paraplegia. Therefore, LSA revascularisation should be considered in the elective setting.…”
Section: Prevention Of Spinal Cord Ischaemia In Open Repairmentioning
confidence: 99%
“…Studies in support of routine preoperative LSA revascularisation show that the coverage of the LSA during TEVAR is associated with an increased risk of stroke, paraplegia and arm ischaemia. Other studies have shown that coverage of the LSA without prophylactic revascularisation is not associated with increased morbidity, supporting those results promoting selective LSA revascularisation during TEVAR [7, 1214]. In this study, we analysed the consequences of intentional LSA coverage during TEVAR with special attention to the development of neurologic complications in a real life, non-selected (“all comers”) population.…”
Section: Introductionmentioning
confidence: 58%